(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article presents the analysis of the Ukrainian linguists in the study of surnames, their lexicographic processing. It is noted that the need for a comprehensive study of the names of residents of specific settlements is of particular interest not only for linguists, but also for historians, ethnographers, and local historians. It has been established that almost half of the names of the inhabitants of Lybokhora village is formed from proper names, especially names that are not common among the villagers, such as: Benda, Kyrei, Klym, Kornii, Magush, Metsei, Onufrii, Sava and the like. More than ten surnames are originated from the names of actions: Palii (from the word palyty ‘to smoke’), Melen (from the word moloti ‘to thresh’), Stupynets (from the word stupati ‘tread’). Several surnames are formed form the names of the animal and plant world: Kobylinets (from the word kobyla ‘mare’), Kaplun (kaplun ‘gelded rooster, which is fed for meat’), Kógut (kogút ‘rooster’, however in the surname the first syllable is stressed, when in the word — the second syllable), Txir (txir ‘ferret’), Kalynovych (kalyna ‘viburnum’), Yablinsky (from the dialect word yablinka ‘apple’), Yablonsky (from the Polish word jab lonka ‘apple’, the Ukrainian word yablunia ‘apple’). There are isolated cases when the origin of the villagers’ surnames lies in the names of concepts: Bedzera (from the Hungarian word bezzeg ‘undoubtedly’); professions: Kovaliv (from the word koval ‘blacksmith’); physical and moral vices of the person: Gluhenky (from the word gluhyi ‘deaf ’), Bahur (from the word bahur ‘debauchee’); items: Nagaiko (from the word nagai ‘short belt whip’), etc. It is verified that most of the surnames of the villagers are formed with the help of suffixal method.